Mangrove trees in the United Arab Emirates during the reign of Sheikh Zayed bin Sultan Al Nahyan 1971-2004 - Alqaydi, Aaesha (Al-Adab Journal, 2024)
The coasts and islands of the United Arab Emirates are green, due to the growth of some trees that can withstand high temperatures and salt water, such as mangroves, which have become the most prominent features of the Emirati environment. The interest of Sheikh Zayed bin Sultan Al Nahyan was marked by the development of a practical program for the interest in agriculture, so he ordered the formation of a special ministry to undertake the tasks of preserving and multiplying agriculture and ensuring its sustainability. His interest was not limited to establishing a private institution concerned with agriculture to undertake all the tasks assigned to it, but he himself took great care of the rare trees by multiplying them. For their environmental importance, the mangroves were foremost among them, which received great attention from the Sheikh Zayed bin Sultan Al Nahyan, because of their great importance and positive impact on the marine or terrestrial environment. This keenness of Sheikh Zayed came as a translation of his awareness of the importance of preserving the agricultural environment to ensure its sustainability for future generations, and in appreciation of the great efforts and pioneering projects through which Sheikh Zayed bin Sultan Al Nahyan implemented his philosophy in preserving the agricultural environment and ensuring its sustainability, This study came to focus on demonstrating the environmental and economic importance of mangroves on the one hand, and the efforts made by the founding leader to preserve and sustain them in the country on the other hand, in addition to highlighting the role played by state institutions in planting and propagating mangroves in particular for their importance in the environmental quality of life and climate in the country. The study relied on a number of local sources represented in contemporary local newspapers, in addition to some reports issued by government institutions concerned with agriculture, which included information on the protection and development of mangroves in the country.